Trial by gas : the British Army at the Second Battle of Ypres - Cassar, George H. (Potomac Books, an imprint of the University of Nebraska Press, 2014)
World War I has long captured the macabre imagination for the seemingly willful manner in which nations sent their young men to die in droves while fighting over essentially the same patch of land for four long years. The vision of those senseless deaths becomes even harsher and more depraved when we consider how many soldiers were killed by poison gas. In May 1915 the long and bloody Second Battle of Ypres gained notoriety for the participants' use of poison gas, the first time the weapon had been used in battle. With both sides realizing the importance of victory in Ypres, moral consideratio.